'He Wears Short Clothes!': Rethinking Rharhabe (c.1715-c.1782) - Peires, Jeff (Journal of southern African studies, 2012)
'Rethinking Rharhabe' is an attempt to grapple with the history of the Eastern Cape in the eighteenth century, a period for which little written and no archaeological evidence is available. The limited information which we have comes from recorded oral traditions, which have heretofore been distorted within a framework of Conventional Wisdom derived from reading history backwards. A closer look at the oral sources reveals significant shifts in the political geography of the Eastern Cape, starting with the revelation that the amaXhosa kingdom, westernmost of all the Eastern Cape kingdoms at the time of the colonial encounter, was formerly located well to the southeast, but moved rapidly westwards during the seventeenth and eighteenth centuries. The dynamics of such radical shifts are explored by considering the life of Rharhabe (c.1715-c.1782), Right-Hand Son of King Phalo (c.1690-1775). Rharhabe's career is here reconstructed by assembling and mapping all sixteen known episodes in his life, rather than the four allowed by the Conventional Wisdom. This more detailed reconstruction shows that Rharhabe's movements were more spasmodic but greater in scope than formerly appreciated. The article concludes by drawing out the implications of the Rharhabe case for the analysis of migrations, state structures and social identities, and for the nature of oral texts as a historical source.